Tinjauan Pustaka Sistematis: Kreativitas Pembelajaran Matematika - Syifa Yuliati; Worowirastri Ekowati, Dyah; Jantung Amelia, Delora; Sumarsono, Puji; Rahmawati Atitik, Agustinah (University of Muhammadiyah Malang, 2024)
Creativity has a vital role in mathematics learning; this has attracted the attention of researchers, thereby increasing publications related to student creativity in mathematics learning. This research aims to describe the trends and contributions of creativity research in Scopus-indexed journals and their opportunities in the future. This research conducted a Systematic Literature Review (SLR), which summarizes research trends and participation related to mathematical creativity published in Scopus-indexed journals. A search was conducted using the keywords